The Influence of Time Management Skills and Learning Motivation on Student Academic Procrastination - Nadilla Aggahra; Zul Afdal (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2025)
This study was initiated by the importance of overcoming academic procrastination behavior that is still widely experienced by students, which has the potential to hinder optimal academic achievement. This study aimed to examine the influence of time management skills and learning motivation on academic procrastination among learners enrolled in the Faculty of Economics and Business, Padang State University. A quantitative methodology was employed in conducting this research with an associative causal design. The population of this study comprised students from the Faculty of Economics and Business at the State University of Padang. The research sample consisted of 96 participants selected using a proportional random sampling technique. To analyze the data, this study utilized multiple linear regression analysis to examine the influence of time management skills and learning motivation on academic procrastination. The coefficient of determination shows that 63.8% of variations in academic procrastination behavior can be explained by time management skills and learning motivation, the remaining variation is influenced by factors outside the scope of this study. This academic work contributes significantly to the development of educational studies by emphasizing the importance of forming time management skills and learning motivation as part of efforts to improve student learning effectiveness